2014
DOI: 10.1097/pai.0000000000000046
|View full text |Cite
|
Sign up to set email alerts
|

Menin Immunoreactivity in Secretory Granules of Human Pancreatic Islet Cells

Abstract: The protein product of the Multiple Endocrine Neoplasia Type I (MEN1) gene is thought to be involved in predominantly nuclear functions; however, immunohistochemistry (IHC) data on cellular localization are conflicting. To further investigate menin expression, we analyzed human pancreas (an MEN1 target organ) using IHC and six antibodies raised against full-length menin or its peptides. In 10 normal pancreas specimens, two independently raised antibodies showed unexpected cytoplasmic immunoreactivity in periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, calpain expression is ubiquitous and the appearance of a C-terminal menin immunoreactive fragment has been described in multiple experimental preparations and tissues, suggesting that the function of C-menin may not be limited to the clustering of nAChRs in neurons. For instance, C-terminal menin immunoreactivity has been found to localize to the membrane of pancreatic islets 40 , and pancreatic β-cells have been reported to express nAChRs 41 . In line with our present findings, this localization could be indicative of the C-menin fragment associated with nAChRs, and suggests that the functional clustering of nAChRs by the C-menin proteolytic fragment may also occur in non-neuronal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, calpain expression is ubiquitous and the appearance of a C-terminal menin immunoreactive fragment has been described in multiple experimental preparations and tissues, suggesting that the function of C-menin may not be limited to the clustering of nAChRs in neurons. For instance, C-terminal menin immunoreactivity has been found to localize to the membrane of pancreatic islets 40 , and pancreatic β-cells have been reported to express nAChRs 41 . In line with our present findings, this localization could be indicative of the C-menin fragment associated with nAChRs, and suggests that the functional clustering of nAChRs by the C-menin proteolytic fragment may also occur in non-neuronal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although menin is primarily a nuclear protein, 27 interacting with multiple nuclear proteins such as Smad protein, JunD, NFkB, FancD2, and MLL1/2, 25,[28][29][30] it is also detectable in cell membrane fraction. 10 However, little is known as to how menin associates with the cell membrane fraction. Coupled with the fact that menin participates in various cell membrane-related functions such as regulating Ras signaling on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our observation, Debelenko et al recently reported that menin is also detected within the secretory vesicles in b cells using electron microscopy. 10 It is also possible that palmitoylated menin binds other molecules or undergoes other chemical modifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations